Instagram, e-Commerce, Media Pemasaran – Kode Etik dan Studi Kasus - Angelina Ervina Jeanette Egeten (AITI, 2017)
Online shopping transaction has become today’s trend in all societies life, it facilitates the customers to make transaction everywhere and every time. A wide range of products offered by online stores can be very attractive for the customers to make such purchase, but there are some many online accounts which do not obey code of ethics in promoting and advertising their products. This issue has turned into the main cause back grounding why the marketing method and advertisement method upon such product must be improved on online media. This research aimed to find out of how to implement code of ethic properly in ecommerce as the product marketing and advertisement media. This research engaged qualitative method with descriptive analysis, observation, case study and literature review to compare the advertisement used by such product which implements code of ethic and vice versa according to the amendment of Indonesian Advertising Ethics Year 2014, while case study for this research was done through Instagram as one of the online media, in order to conduct the analysis phase upon the implementation of the code of ethics in e- commerce. This research led into a result that several instagram accounts had not applied code of ethics in promoting and advertising their products of which was not in accordance with the prevailingIndonesian Advertising Ethics, while the other instagram accounts had implemented proper code of ethics, in which by this implementation, it could bring positive impact and fairness in product selling and marketing.